WATER FORMATION MANAGEMENT OPTIMIZATION FOR RESERVOIR X BY USING RESERVOIR SIMULATION AND WATER TREATMENT - ORIG SETIANTO HARTOYO
Water formation treatment needs to be conducted by knowing the condition and performance which is associated to the reservoir and the surface of separation equipment. Therefore the design of water treatment should consider the integrated components starting from the reservoir performance to the water treatment facilities. The most important thing in treating water formation is the recipient environments that consist of the surface and the reservoir recipient. If the produced water will be discharge as waste water into the surface recipient it should be treated to meet the water quality standard as stated in PerMenLH No. 04 of 2007. If the produced water will be injected into the reservoir, the reservoir response should be considered. In this thesis both situations have been studied and followed by economic analysis as the important parameters to decide the best scenario. The capacity of water treatment facilities is depend on the expected produced water and the number of production wells. In this thesis the number of production wells is optimized by applying ECLIPSE Simulator. Similarly the effect of water injection and the required injection wells are also conducted. Based on the result of simulation the optimum scenario of water treatment is decided by treating and disposing produced water to the surface recipient. However, this scenario is feasible if the oil prices more than U.S. $ 40/barrel.